The Diversity of Legume-Nodulating Bacteria from Several Agroecosystems in Sumberjaya, Lampung - Sri Wedhastri; Yuliana Prahastiwi; Jaka Widada; Donny Widianto; Siti Kabirun (Universitas Gadjah Mada, 2013)
Bacteria that capable of forming root nodules on legumes are known as Rhizobia. They have also known as Legume- Nodulating Bacteria (LNB). They can fi x nitrogen from the atmosphere. Diversity of Legume-Nodulating Bacteria is affected by biotic factors (such as their genetic factors, plants, and competition with the other soil microbes) and abiotic factors (such as land use, soil’s temperature, pH, chemistry and soil’s properties). The aim of this experiment is to know the diversity of eleven Legume- Nodulating Bacteria based on their phenotypic and genotypic characters. The eleven LNB used in this experiments were isolated from several agroecosystems in Sumberjaya, Lampung. The analysis of these LNB diversity were carried out by characterizing both phenotypic and genotypic properties. The diversity analysis showed that the eleven LNB isolates had high diversity, based on nodule formation, and classifi ed into two groups of cross inoculation group. Key words: Rhizobia, phenotypic diversity, genotypic diversity